2003
DOI: 10.1172/jci200319301
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal germinal center reactions in systemic lupus erythematosus demonstrated by blockade of CD154-CD40 interactions

Abstract: To determine the role of CD154-CD40 interactions in the B cell overactivity exhibited by patients with active systemic lupus erythematosus (SLE), CD19 + peripheral B cells were examined before and after treatment with humanized anti-CD154 mAb (BG9588, 5c8). Before treatment, SLE patients manifested activated B cells that expressed CD154, CD69, CD38, CD5, and CD27. Cells expressing CD38, CD5, or CD27 disappeared from the periphery during treatment with anti-CD154 mAb, and cells expressing CD69 and CD154 disappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(61 citation statements)
references
References 89 publications
3
56
0
2
Order By: Relevance
“…6,32 Earlier studies have provided indirect evidence to indicate the role of T FH cells in promoting human autoimmunity, e.g., production of pathogenic autoantibodies in SLE patients caused by dysregulated GC reactions, 31,48 presence of the aggregates of T and B cells containing plasmablasts in the kidneys of patients with lupus nephritis 49 and reduced GC reactions upon blocking CD40L-CD40 interactions in patients with active SLE. 50 Recent studies have further provided clearer evidence on the role of T FH cells in promotion of both systemic and organ-specific autoimmune diseases in humans. [51][52][53][54][55] Simpson et al 51 performed an elegant study investigating the role of T FH cells in patients with SLE and Sjogren's syndrome.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…6,32 Earlier studies have provided indirect evidence to indicate the role of T FH cells in promoting human autoimmunity, e.g., production of pathogenic autoantibodies in SLE patients caused by dysregulated GC reactions, 31,48 presence of the aggregates of T and B cells containing plasmablasts in the kidneys of patients with lupus nephritis 49 and reduced GC reactions upon blocking CD40L-CD40 interactions in patients with active SLE. 50 Recent studies have further provided clearer evidence on the role of T FH cells in promotion of both systemic and organ-specific autoimmune diseases in humans. [51][52][53][54][55] Simpson et al 51 performed an elegant study investigating the role of T FH cells in patients with SLE and Sjogren's syndrome.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…CD40 in lipid raft is decreased on activated B cells from SLE [49], but functionally active CD154 (CD40L) expression on SLE B cells is increased [50,51]. CD154 transgenic mice have increased number and enhanced survival of B cells [52].…”
Section: Surface Molecules On B Cellsmentioning
confidence: 99%
“…CD154 transgenic mice have increased number and enhanced survival of B cells [52]. Spontaneous proliferation and Ig secretion of peripheral B cells from active lupus patients could be inhibited by blockade of CD154-CD40 interaction [50]. Ligation of CD40 with CD154 provides an important co-stimulation signal and plays an essential role in GC reaction.…”
Section: Surface Molecules On B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is to interfere with the induction and maintenance of GC reactions that produce autoantigen-specific memory and Ig-secreting plasma cells by blocking CD40-CD154 interactions. Results from a recent uncontrolled open-label study showed that treatment of SLE with a humanized monoclonal antibody (mAb) to CD154 (BG9588, 5c8) significantly reduced serum autoantibodies and proteinuria, and also reduced the disease activity score on the SLE Disease Activity Index (52). Whereas the antibody used in these studies elicited an increase in the frequency of thrombotic events, and thus conferred unacceptable side effects, the use of another mAb to CD154 (24-31, IDEC-131) in SLE is apparently not associated with an increased frequency of thrombosis, although minimal efficacy of this latter mAb has been noted (53).…”
Section: Implications For Therapymentioning
confidence: 99%